Estetika dalam Kosmis sebagai Pembelajaran dan Konservasi Gamelan di Era Modern - Wijayanto, Wasis; Fifit Fidyastuti (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2025)
This research aims to deeply understand the function of Saron in the composition of Javanese gamelan and uncover the symbolism inherent in the instrument in the people of Central Java. The Saron, as the core instrument of the gamelan, not only serves as the main melody producer, but also has a rich symbolic meaning. This study uses a qualitative approach with ethnographic methods and literature studies. Data collection was carried out through participatory observation in various gamelan performances at traditional and ritual events in Central Java, as well as in-depth interviews with pengrawit (gamelan players) and local cultural figures. In addition, literature studies from art and cultural journals relevant to gamelan and traditional musical instruments of Central Java were also carried out. The collected data was analyzed using descriptive methods of interpretive analytics. The results of the study show that Saron not only functions as a sound producer with its distinctive characteristics, but also as a symbolic representation that connects society, culture, and spirituality in the Javanese context. Saron game techniques and improvisation express a wide range of emotions. Through its role in gamelan, rituals, and social life, Sarons are a reflection of cultural identity, a guardian of harmony, and a messenger of life.